Comparative efficacy of rTMS on different targets in Alzheimer’s disease: a systematic review and meta-analysis - Zhang, Yushu; Dong, Ke; Yang, Jiajia; Guo, Qifan; Zhao, Yan; Zhu, Xiaoxia; Liu, Dongxu; Liu, Peng (Frontiers in Aging Neuroscience, 2025)
BackgroundRepetitive transcranial magnetic stimulation (rTMS) is emerging as a promising non-invasive intervention for Alzheimer’s disease (AD), yet therapeutic outcomes remain inconsistent across studies. This meta-analysis aimed to evaluate the cognitive benefits of rTMS in AD patients, with a specific focus on stimulation targets and protocols variations.MethodsA systematic literature search was conducted in PubMed, Web of Science, Embase, and Cochrane Library for relevant English-language studies published up to 31 May 2024. Cognitive outcomes were assessed using the Mini-Mental State Examination (MMSE) and Alzheimer’s Disease Assessment Scale-Cognitive Section (ADAS-Cog). Data were pooled using a random-effects model, with standardized mean difference (SMD) or mean differences (MD) and 95% confidence intervals (CI) calculated. Subgroup analyses were performed to examine the effects of stimulation targets, protocol variations and population demographics on rTMS efficacy.ResultsTwenty-two studies involving 874 participants were included in this meta-analysis. Overall, rTMS significantly improved cognitive function (SMD = 0.27; 95% CI = 0.14–0.41; p < 0.0001), showing that the efficacy of rTMS varied by stimulation target and protocol. Stimulation of the dorsolateral prefrontal cortex (DLPFC) led to significant cognitive improvement (SMD = 0.49, 95% CI = −0.26 to 0.73; p < 0.0001), whereas bilateral DLPFC stimulation showed no significant improvement (SMD = 0.13; 95% CI = −0.40 to 0.66; p = 0.62). Stimulating the parietal lobe or associated regions produced moderate cognitive benefits (SMD = 0.29; 95% CI = 0.03–0.55; p = 0.03). Notably, multi-target stimulation over the bilateral DLPFC, parietal lobes, Wernicke’s area, and Broca’s area also showed substantial cognitive improvement (MD = 2.85; 95% CI = 1.69–4.00; p < 0.00001). Additionally, subgroup analysis based on geographical background revealed greater effects in studies conducted in Asia (SMD = 0.40, 95% CI = 0.14–0.65; p < 0.003).ConclusionrTMS is an effective intervention for cognitive enhancement in AD, with its efficacy significantly influenced by stimulation target and protocol. Notably, the greater cognitive benefits observed in Asian populations suggest a potential role of genetic and demographic factors that warrant further investigation. These findings contribute to the development of optimized, personalized rTMS protocols for AD treatment.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, CRD42023434084.